(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study discusses finance related to banks that have high CARs with banks that have low CARs that are projected through ROA and ROE in banks registered in the Kompas 100 index for the 2012-2017 period. The sample of this study consisted of 7 banks contained in the Kompas 100 index for the 2012-2017 period. This research method is a quantitative and descriptive method using a paired sample test and an Anova test with the use of SPSS 24.0 software. The results showed differences in ROA performance in banks that have a high CAR and banks that have a low CAR and a difference in ROE performance in banks that have a high CAR and banks that have a low CAR.